GAMBARAN PERILAKU PERAWAT DALAM MEMBUANG LIMBAH MEDIS DAN NON MEDIS DI RUMAH SAKIT UMUM DAERAH KABUPATEN ACEH TAMIANG TAHUN 2013 - Muchsin alatas (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Medical waste is the infectious and dangerous substances that must be managed properly in order not to become the source of new infectious to the people around the hospital and for health officer themselves. Based on the preliminary survey in general  hospital  district of Aceh Tamiang still found medical waste mixed with non-medical waste, although the provision of information on medical waste has been given.       The research objectif was to describe the behavior of nurses in throwing away medical waste and non-medical waste in general  hospital  district of Aceh Tamiang. This type of reseach was descriptive quantitative taken of sample by probability sampling with measures proporsional. The population in this study were all nurses have task  rooms medical waste   in general  hospital  district of Aceh Tamiang as many as 213 nurses and the number of respondens sample taken many as 60 nurses. The data were gathered by using questionnaires. The results of reseach that the characteristics description of the respondents is the majority of responden aged 26-30 years by 33,3%. The gender  majority of respondents were female in 68,3%. the majority of respondents had school D-III nursing level 46,7.The majority of respondents work period 5-9 years in 45,0%. The majority of respondents have training about medical waste in 66,7%, Sources of information from mass media in either cathegory are 78,3%. Sources of information from environtment  health officials  in either cathegory are 71,7%. Knowladge of respondents are good enaugh that moderate category  63,3%. The attitude of the respondents in the less category as much as 55,0%. Respondents actions to in throwing away medical waste and non-medical waste is still low because in the category of less is 58,3%. From the results of the study suggested that leadership in general  hospital  district of Aceh Tamiang to conduct outreach and controling to health officials and nurses in manage medical waste and non-medical waste.